Preparation of Composite Derived from Banana Peel Activated Carbon and MgFe2O4 as Magnetic Adsorbent for Methylene Blue Removal - Arie Hardian; Rosi Rosidah; Senadi Budiman; Dani Gustaman Syarif (Jurnal Kimia Sains dan Aplikasi, 2020)
Methylene blue (MB) is one of the dyes used often by the textile industry. Therefore, MB residual is contained in the textile industry waste. MB can irritate, leading to permanent eye and animal injuries; therefore, the textile industry waste concentration must be degraded before disposed to the environment. MB residual in textile industry waste can be treated with activated carbon adsorption. However, the adsorption method is less effective because the deposition takes a long time. This research aims to make activated carbon composites from banana peels and magnesium ferrite (BPAC/MgFe2O4) using the coprecipitation method to obtain activated carbon with magnetic properties (magnetic adsorbent). The obtained composite was characterized using X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), Energy Dispersive X-Ray (EDX), and Surface Area Analyzer. The adsorption performance of methylene blue on composites was evaluated with variations in pH, concentration, contact time, determination of adsorption isotherms, and kinetics of adsorption. XRD analysis results showed the composite has a cubic crystal structure with a crystallite size of 7.69 nm. SEM analysis results show the surface morphology has pores with irregular shapes. EDX analysis results showed that the composition of activated carbon composite was 65.56% carbon, 2.28% Mg, 5.50% Fe, and 26.66% O. The results surface area analysis showed a composite surface area of 88.134 m2/g. Composite adsorption performance showed maximum results at pH 7, variations in concentration at 10 ppm, and contact time 180 minutes with adsorption capability of 99.26%. Determination of the adsorption isotherm follows the Freundlich adsorption isotherm model with a pseudo-second-order adsorption kinetics model. The obtained BPAC/MgFe2O4 composite can potentially be a magnetic adsorbent capable of adsorbing methylene blue in an aqueous solution.